Lifestyle change using the health belief model to improve cardiovascular risk factors among postmenopausal women. - Huang, Mary Soo Lee; Kandiah, Mirnalini; Yassin, Zaitun; Abedi, Parvin (2011)
Globally, CVD is the number one cause of death and are projected to remain so in the future. The main cause of death in Iran is CVD which accounts for almost half (42%) of total deaths. It was a randomized controlled trial to determine the impact of a 6-month lifestyle changes using the Health Belief Model (HBM) on cardiovascular risk factors in sedentary, postmenopausal Iranian women. This study started on June 2007 and completed on May 2008. A total of 67 healthy and sedentary postmenopausal women recruited and randomly assigned to two groups namely; exercise (38), and control (29). Over the six months follow-up, the intervention group received five educational sessions (one face to face education in the first session and one in the 3rd month and three lecture discussion classes with slide demonstration) at the first month about physical activity according to the Health Belief Model. Every participant received a telephone call at the end of each month starting with the second month to remain on the exercise. Pre-intervention and post-intervention HBM components, anthropometric measurements, blood pressure (BP), blood lipids and physical activity were assessed. Data analyzed using the SPSS version 15. Descriptive, univariate and multivariate statistics were used. Results: The women in the exercise group experienced significant decrease in their LDL (-15mg/dl), FBS (-7.4mg/dl), and increased their physical activity compared to the control group (272 minutes/week, p=0.02). All components of HBM except for knowledge improved significantly in the exercise group compared to the control group (p=0.001). Lifestyle change intervention using the HBM can be an effective means of reducing cardiovascular risk in obese and sedentary postmenopausal women.